2014
DOI: 10.1352/1944-7558-119.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Self-Injury, Aggression, and Stereotyped Behavior Among Young Children At Risk for Intellectual and Developmental Disabilities

Abstract: Before the 1990s, research on the early identification and prevention of severe behavior disorders (SBDs), such as aggression, self-injury, and stereotyped behavior, among young children with intellectual and developmental disabilities (IDD), was mostly done with children 3 years or older. More recent work suggests that signs of SBDs may occur as early as 6 months in some infants. The present study combined a cross-sectional and longitudinal approach to examine SBDs in 180 young children aged 4–48 months recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 65 publications
5
73
2
1
Order By: Relevance
“…The relative risk of a child with ASD engaging in SIB at 24 months was almost two-fold that of a child without a diagnosis. These data are consistent with previous work and suggest that SIB emerges early in life, can be persistent, and is prevalent among children with ASD (e.g., Baghdadli et al 2008; Berkson et al 2001; Schroeder et al 2014). Almost half of the participants who engaged in SIB at Time 1 persisted in engaging in SIB at follow up.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The relative risk of a child with ASD engaging in SIB at 24 months was almost two-fold that of a child without a diagnosis. These data are consistent with previous work and suggest that SIB emerges early in life, can be persistent, and is prevalent among children with ASD (e.g., Baghdadli et al 2008; Berkson et al 2001; Schroeder et al 2014). Almost half of the participants who engaged in SIB at Time 1 persisted in engaging in SIB at follow up.…”
Section: Discussionsupporting
confidence: 91%
“…Only two sets of prospective cohort studies and one direct observation study have investigated early SIB among young children at risk for developmental delay (Rojahn et al 2015; Schroeder et al 2014) and with developmental disabilities (Berkson 2002; Berkson et al 2001; Richman and Lindauer 2005) that included some children with ASD. With a sample of young children at risk for a behavior disorder such as aggression or SIB from Peru (n = 180; age = 4–48 months), Schroeder et al (2014) examined potential risk factors across three time points. Results indicated that SIB varied by diagnostic group status over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational exposures such as vibration [26], mechanical influences such as heavy lifting and weight [27], unhealthy lifestyle such as lack of exercise [28] and smoking [29,30], and the long use of non-Swedish and non-Japanese cars [31] have been blamed for contributing to disc degeneration and associated herniation. Trauma is also suggested as a contributor to IDD [32,33]. On the other hand, genetic contributions have been confirmed by identifying the polymorphisms of many key genes involved in the degeneration of IVD, including a disintegrin and metalloprotease with thrombospondin motif (ADAMTS)-4 [34], ADAMTS-5 [35], matrix metalloproteinase (MMP)-2 [36], MMP-3 [37], MMP-9 [38], MMP-14 [39], aggrecan [40], and vitamin D receptor [41,42].…”
Section: Etiology Of Iddmentioning
confidence: 99%
“…Occupational exposures such as vibration [14], mechanical influences including heavy lifting and weight [15], lifestyle factors such as lack of exercise [16], and the long use of nonJapanese cars [17] are known to promote IVD degeneration. Injuries associated with lifting or trauma [18,19] and tobacco use [20,21] have been also reported to be involved in the pathology of IDD. However, there is accumulating evidence that these environmental factors may explain only a small portion of IDD, and heredity is predominant and probably accounts for more than 70% of an individual's risk for degenerative disc disease [22].…”
Section: Etiology Of Iddmentioning
confidence: 99%